2022
DOI: 10.3390/genes13020241
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Influence Neurofilament Deposition in ALS iPSC-Derived Motor Neurons

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease in which upper and lower motor neuron loss is the primary phenotype, leading to muscle weakness and wasting, respiratory failure, and death. Although a portion of ALS cases are linked to one of over 50 unique genes, the vast majority of cases are sporadic in nature. However, the mechanisms underlying the motor neuron loss in either familial or sporadic ALS are not entirely clear. Here, we used induced pluripotent stem cells derived from a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Motivated by our long-term interest in using human iPSC-derived microglia for the study of ALS pathophysiology, we chose to compare the microglia derivation methods described by Douvaras and colleagues ( Douvaras et al, 2017 ) and McQuade and coworkers ( McQuade et al, 2018 ), because either one or the other of these widely used methods have been utilized recently to model the involvement of human microglia in ALS pathophysiology ( Allison et al., 2022 ; Kerk et al, 2022 ). Both of these derivation protocols achieve the robust generation of microglia under serum-free conditions and in the presence of defined cytokines ( Douvaras et al, 2017 ; McQuade et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by our long-term interest in using human iPSC-derived microglia for the study of ALS pathophysiology, we chose to compare the microglia derivation methods described by Douvaras and colleagues ( Douvaras et al, 2017 ) and McQuade and coworkers ( McQuade et al, 2018 ), because either one or the other of these widely used methods have been utilized recently to model the involvement of human microglia in ALS pathophysiology ( Allison et al., 2022 ; Kerk et al, 2022 ). Both of these derivation protocols achieve the robust generation of microglia under serum-free conditions and in the presence of defined cytokines ( Douvaras et al, 2017 ; McQuade et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The elucidation of the roles of microglia during the progression of ALS, and other neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease, has benefitted from the recent development of robust and reliable methods to generate microglia from human iPSCs, including iPSCs derived from patients affected by familial forms of these diseases and their matching genome-edited isogenic iPSCs. To date, the published studies using human iPSC-derived microglia to model ALS pathophysiology, which have used either one or the other derivation method investigated in the present study ( Allison et al, 2022 ; Kerk et al, 2022 ), have not provided information on the subcellular composition of the microglia cultures that were examined. There is a growing need to gather more information on the diversity of different in vitro microglia experimental systems, stemming from the demonstrated spatial heterogeneity of microglia in vivo ( DePaula-Silva et al, 2019 ; Grabert et al, 2016 ; Li et al, 2019 ; Masuda et al, 2019 ; Masuda et al, 2020 ; Stratoulias et al., 2019 ; van der Poel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, human iPSCs were induced to undergo commitment to the myeloid lineage and differentiation into microglia following the methods by Douvaras and colleagues (Douvaras et al ., 2017) or McQuade and coworkers (McQuade et al ., 2018). Both of these methods have been used recently to model the involvement of human microglia in ALS pathophysiology (Allison et al ., 2022; Kerk et al ., 2022). In the context of the present study, we shall hereafter operationally refer to microglia generated using the Douvaras et al protocol as ‘Douvaras-microglia’, and microglia generated using the McQuade et al method as ‘McQuade-microglia’.…”
Section: Resultsmentioning
confidence: 99%
“…The elucidation of the roles of microglia during the progression of neurodegenerative diseases, including ALS, has benefitted from the recent development of robust and reliable methods to generate microglia from human iPSCs, including iPSCs derived from patients affected by familial forms of these diseases and their matching genome-edited isogenic iPSCs. To-date, the few published studies using human iPSC-derived microglia to model ALS pathophysiology, which have used the two derivation methods investigated in the present study (Allison et al ., 2022; Kerk et al ., 2022), have not provided information on the subcellular composition of the microglia cultures that were examined. There is a growing need to gather more information on the diversity of different in vitro microglia experimental systems, stemming from the demonstrated spatial heterogeneity of microglia in vivo (Grabert et al ., 2016; DePaula-Silva et al ., 2019; Li et al ., 2019; Masuda et al ., 2019; Stratoulias et al ., 2019; van der Poel et al ., 2019; Masuda et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, downregulation of two exclusively spinal cord and CSF-expressed miRNAs, miR-92a-3p, miR-9-5p, bind to recognition elements in the 3’UTR of NEFH to increase the expression of NEFH mRNA transcripts and NF-H protein levels in people with ALS 55,56 . Moreover, there is emerging evidence which suggests that microglial-secreted protein factors can influence NEFH transcript expression and contribute to NF-H inclusion pathology, albeit in the absence of NEFH mutations 57 . Therefore, future studies should build on what we have reported here by incorporating genetic evidence of missense tail mutations with proteomic and transcriptomic data to determine if the aberrant stoichiometry of NF-H is due solely to the action of the mutation on phosphorylation sites within the tail or is a product of a larger interaction between miRNA, protein and glial targets.…”
Section: Discussionmentioning
confidence: 99%